Energy analysis and performance assessment of a hybrid deep borehole heat exchanger heating system with direct heating and coupled heat pump approaches. (15th January 2023) - Wang, Zeyuan; Wang, Fenghao; Liu, Jun; Li, Yizhen; Wang, Ming; Luo, Yongqiang; Ma, Longxia; Zhu, Chao; Cai, Wanlong
Highlights: A transient model for a hybrid DBHE heating system is first developed in TRNSYS. Direct heating and coupled GSHP approaches are designed in hybrid heating system. Importance of direct heating approach and dynamic load characteristic is assessed. Energy shifting behavior of different components is observed over 10-year operation. Parabolic soil temperature isotherm appears at the end of heating season in reality. Abstract: The deep borehole heat exchanger (DBHE) coupled ground source heat pump (GSHP) system is widely developed in recent years to extract geothermal energy for building heating. However, its operating mechanism and energy flows within different components have not been comprehensively investigated. Meanwhile, the high outlet temperature of DBHE has the potential to meet the direct heating requirement but may exceed the GSHP's temperature threshold. Therefore, this study first presented a hybrid DBHE heating system transient model with direct heating and coupled GSHP approaches using TRNSYS and MATLAB software. The novelty of this system is that DBHE was also coupled with a heat exchanger (HEX) to realize direct heating. Taking a residential building in Xi'an and DBHE with the depth of 2000 m as a scenario, the operation behavior and energy performance of the system were analyzed. The results showed that HEX will operate for several days before operating GSHP at the beginning of heating season, and annual HEX operating time gradually decreases from 27.1 days to 8.8 days over 10 years. Annual energy fraction of heat extracted from the soil by the HEX and GSHP in the total heating demand gradually decreases from 0.14 to 0.05 and increases from 0.72 to 0.78 over 10 years, respectively. Further, the importance of HEX in system performance was evaluated. Compared with the hybrid system, the GSHP's COP will be overestimated by 11.3 % and the heat extraction amount will be significantly underestimated when HEX is not designed in the DBHE system. Moreover, the effects of different building heating load characteristics (including actual load and constant load) on system performance were discussed. It was found that the minimum inlet temperature of DBHE during the heating season under constant load will be overestimated, with a maximum deviation of 8.4 °C. Dynamic building load also results in a parabolic soil temperature isotherm at the end of heating season.